2017
DOI: 10.1039/c6ra24927b
|View full text |Cite
|
Sign up to set email alerts
|

Porous hollow carbon nanofibers derived from multi-walled carbon nanotubes and sucrose as anode materials for lithium-ion batteries

Abstract: Porous hollow carbon nanofibers with tunable shell thicknesses from 2.5 to 13.5 nm have been synthesized via a hydrothermal approach by using multi-walled carbon nanotubes as the scaffolds and sucrose as carbon source. The thin, porous and non-graphitic carbon shells are revealed by X-ray diffraction, Raman spectra, high-resolution transmission electron microscopy, and nitrogen adsorption isotherms. In comparison with the pristine multi-walled carbon nanotubes, the as-prepared porous hollow carbon nanofibers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A recent report indicated that the G band represents the graphitization degree of materials, structural defects are reflected by the D band [31]. To our best knowledge, the ID/IG ratio represents structural disorder in graphitic materials [32]. As observed from Figure 3a, the value of NSG (1.09) was lower than that of SG (1.15) and NG (1.29), indicating the increasing graphitic degree of NSG which may be derived from the "self-repairing" of intermediate products under experimental conditions with the repairing of partial sp 2 -bonded C atoms.…”
Section: Characterization Of Electrocatalystsmentioning
confidence: 92%
“…A recent report indicated that the G band represents the graphitization degree of materials, structural defects are reflected by the D band [31]. To our best knowledge, the ID/IG ratio represents structural disorder in graphitic materials [32]. As observed from Figure 3a, the value of NSG (1.09) was lower than that of SG (1.15) and NG (1.29), indicating the increasing graphitic degree of NSG which may be derived from the "self-repairing" of intermediate products under experimental conditions with the repairing of partial sp 2 -bonded C atoms.…”
Section: Characterization Of Electrocatalystsmentioning
confidence: 92%
“…Non-graphitizable carbon with a disordered (pseudographite) structure along its c-axis is referred to as HC. 34 The HC has a structure with synthetically controllable properties and high porosity, and it can be derived from biomass, 108 pyrolyzed sucrose, 109 and phenolic cured resins. 110 The structures of HC are cross-linked to maintain its amorphous structure and prevent the development of a graphitic structure.…”
Section: Hard Carbon Anodesmentioning
confidence: 99%